Risk factors and preventive role of vaccination in adult tetanus fatality: a systematic review of reported cases (1990-2024) and meta-analysis - Selin Kolsuz; Deniz Güllü; Koçer Dilan Karahan; Önder Ergönül (International Journal of Infectious Diseases)
Objectives: This study identifies key risk factors for fatality among adult tetanus patients, assesses the impact of vaccination status and antibody levels on disease severity and outcomes in tetanus cases. Despite widespread vaccination, fatality rates remain high due to diagnostic and management challenges. Design/Methods: A meta-analysis of 182 tetanus cases from 36 countries, published since 1990, was conducted. The analysis focused on risk factors such as autonomic dysfunction, opisthotonus, incubation time, diabetes mellitus, cardiovascular diseases, and dermatological conditions. Results: Key risk factors for fatality included autonomic dysfunction, opisthotonus, shorter incubation periods, diabetes mellitus, cardiovascular diseases, and ulcers and dermatological conditions. Interestingly, fatalities occurred in patients with antibody levels above the proposed protective threshold, showing that serological evidence of immunity is not absolute. Importantly, patients with a complete vaccination history experienced less severe disease, and no fatalities were observed among those who had received a full course of childhood vaccinations. Conclusions: The findings highlight the importance of maintaining up-to-date vaccination schedules to reduce the severity of disease and improve outcomes in tetanus cases. The results suggest that while immunity may not always prevent infection, prior vaccination significantly mitigates disease severity. Given that immunity may not be entirely protective and up-to-date vaccinations seem to improve the outcomes, prompt diagnosis and effective booster vaccinations are crucial to further reduce mortality in tetanus patients.